The Effect of Compositional Optical Analysis of ZnO/TiO2 Composites In a Sunscreen Product - Maritza Syalsabilla; Fuad Sofaturahman; Mira Syuriyani; Lia Rifka Septiana; Nadia Raisa Aryani; Riri Jonuarti; - Ratnawulan; Rahmat Hidayat (Department of Physics – Universitas Negeri Padang UNP, 2023)
TiO2 and ZnO are active components in commercialized physical sunscreens that have a broad protective spectrum, which includes UVB and UVA. The combination of ZnO/TiO2 composites has more effective performance in blocking Ultra Violet rays in a wide wavelength range compared to ZnO or TiO2 alone. However, the high refractive index of TiO2 can cause a white cast. To solve the issue, a cream was created by incorporating antioxidants such as Virgin Coconut Oil (VCO). The purpose of this study is to determine the effect of the ZnO/TiO2 composite optical composition on visible and ultra violet light. Three composition comparisons were investigated in the study: ZnO/TiO2 10% added VCO, ZnO/TiO2 5% added VCO, and ZnO/TiO2 5% without VCO. UV-vis spectroscopy characterization showed that the ZnO/TiO2 composite absorbed more effectively in the ultra violet range than in visible light, and the greatest absorption and maximum reflectance are in the UVA1 range. The higher the concentration of ZnO/TiO2 in the cream composition, the higher the cream's absorption and reflection peaks. The reflectance in the visible light region is low, between 30% and 40%, implying that visible light passes through the sunscreen cream 70% to 80% of the time. As a result, the higher the ultra violet reflectance of the physical sunscreen cream, the lower the transparency. The higher the concentration of ZnO/TiO2, the greater the band gap value of the physical sunscreen, in the range of 3.1–3.5 eV